Novel Approaches to Enhance Solubility Medicine: Pharmaceutical sciences- Industrial pharmacy - Kumar Yadav, Anurag; Pandey, Harsh Kumar; Shiven, Aditya (International Journal of Life Science and Pharma Research, 2023)
The solubility enhancement of poorly aqueous soluble drugs presents a significant challenge in pharmaceuticalformulation. Liquisolid technology, also known as powdered solution technology, has emerged as a promising approach toenhance the solubility and bioavailability of such drugs. This paper provides a detailed discussion of the novel approachesemployed within the framework of Liquisolid technology to overcome solubility limitations. The study explores the principles,advantages, and applications of Liquisolid technology in drug formulation, highlighting its potential to revolutionize oralmedication delivery. This research aims to investigate the effectiveness of Liquisolid technology in enhancing drug solubility,elucidate its underlying mechanisms, and evaluate its impact on drug dissolution, bioavailability, and therapeutic outcomes. Theobjectives are to review the background and challenges associated with poor solubility of drugs, introduce the concept ofLiquisolid technology and its principles, discuss the advantages and benefits of Liquisolid technology in solubility enhancement,explore the formulation strategies and key components involved in Liquisolid formulations, evaluate the in vitro and in vivoperformance of Liquisolid systems, and identify future research directions and potential applications of Liquisolid technology inpharmaceutical development. Through this comprehensive analysis, the study aims to provide valuable insights into the novelapproaches based on Liquisolid technology for enhancing drug solubility, facilitating the development of effective and efficientdrug delivery systems. Liquisolid technology, a novel approach to solubility enhancement, offers promising advantages overconventional techniques. It involves solubilizing poorly aqueous soluble drugs using surfactants, then incorporating thesesolubilized drugs into a carrier system or powdered solution. The powdered solution facilitates the conversion of the solubilizeddrug into solid residues, which can be further processed into different dosage forms.